Pott’s paraplegia-satisfactory outcome in spite of poor prognostic factors, treated by a novel surgical technique of posterior spinal stabilization and anterolateral decompression with bone graft fusion: a case report - Sarkar, Rajib; Sarkar, Samriddhi; Pramanik, Atanu; Ali, S. Imran; Mukherjee, Somdeep (International Journal of Research in Medical Sciences, 2024)
A case of Pott’s paraplegia of sudden onset and of more than two months duration in an aged female, treated by a novel surgical technique of anterior decompression and local kyphotic angle correction by spinal pedicular fixation is presented here. A 52 year female with Pott’s paraplegia, ASIA-A with sphincters involvement and with flexor spasm, was treated by surgical intervention, in a single operation of two stages, the first by provisional posterior pedicular fixation and the second stage by anterolateral decompression and correcting the local kyphotic angle by cyclic changing the rods in increments of 5 degrees in compressive mode. The paravertebral abscess of opposite side was sucked out and at the end a tricortical bone graft harvested from iliac crest was impacted in between the space created by pedicular fixation maneuver in course of correcting kyphosis. There was steady dramatic improvement of clinical and neurological status within three weeks. Kyphotic correction was maintained with anterior tricortical interbody bone graft impacted in position. The novel surgical technique that is adopted for decompression, drainage including paravertebral abscess of opposite side, debridement and local kyphotic angle correction along with interbody bone graft fusion, in this case, offered a satisfactory outcome in spite of poor prognostic factors.